Evaluation of Serum Lipid Profile and Renal Function Levels in Iraqi Patients with Chronic Kidney Disease (CKD) - Lateef , Ahmed Salih; Alkubaisi, Mithal R; AL-Hitti, Ismail K.; AL-Rawi, Khalid F.; Freah, Yousef Talleb; Khalaf, Ahmed Jumaa; Ali, Marwan Raad; Khalaf, Ahmed Faisel; Abdullah, Abdullah Abd-Aleem; Dawood, Maher Hameed (Iraqi Journal of Science, 2024)
Chronic Kidney Disease (CKD) has been raised as a public health state worldwide and is associated with increased cardiovascular morbidity and mortality. The aim of the study was to assess serum lipid profile levels, renal function and glucose in CKD patients undergoing hemodialysis. A total of 50 patients (23 males and 27 females) with CKD attending the hemodialysis at Kidney Unit in Al-Ramadi Teaching Hospital, Anbar Iraq and of ages ranging between 20 -85 years, were sustained for this research. The patients were classified into three categories with their mean age of 65.71±1.98 years. Eleven healthy adults were also recruited in this study with mean age of 37.00±15.56 years as control group. The study included measuring biochemical markers such as glucose, total cholesterol(TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), very-low-density lipoprotein (VLDL) , creatinine and urea by using automated chemistry analyzer by Abbott/USA. The outcomes of this study showed that the urea and creatinine levels increased significantly, whereas HDL-C level significantly decreased in the patients as compared with control group. However, TC and LDL-C showed slightly lower levels which were within the normal limits in the control group. While TG, VLDL and glucose levels showed non-significant changes in CKD patients as compared with control (P ≤ 0.05). In addition, all parameters revealed no significant changes in males as compared with females group (P ≤ 0.05). Depending on age, only creatinine level showed significant change in 20-40 years age group as compared with 61-85years age group (p <0.05). Finally, abnormal lipid metabolism may probably be an independent risk factor for the progression of renal disease.